Bibliometric Analysis of the Journal of Health and Nursing Management - Filiz Kantek; Hakan Kurnaz; Hande Yeşilbaş (Association of Nurse Managers, 2020)
INTRODUCTION: The aim of this study is to investigate the characteristics and development of Journal of Health and Nursing Management. METHODS: The bibliometric analysis method was used in the study. From the year that SHYD started its first publication, 101 articles were reviewed in the five-year period (2014-2018). The study data were obtained by using the data collection form developed by the authors. In the analysis of the data, descriptive statistics, t test and correlation analysis were used.Ucinet / Netdraw program was used for visualizing the data. RESULTS: Of the studies included in the research, 68.32% were research articles (69 studies) and 31.68% of them were review (32 studies). It was found that 101 studies were produced by 173 different authors and 84 different institutions, 44 authors had two and more publications, and the number of authors in publications ranged from 1 to 6.The highest number of studies (45 studies) with the institution of Istanbul University, the most productive author Serap Altuntaş (9 studies) was determined. The most frequently used keywords were 'Nursing','Nurse', 'Hospital' and 'Nurse Executive'. The total number of citations of the studies was 229 and 51.49% (52 studies) were not cited. DISCUSSION AND CONCLUSION: This research has provided important information for the journal's history and further development for the readers and next authors of the Journal of Health and Nursing Management.